2014
DOI: 10.1111/1440-1630.12133
|View full text |Cite
|
Sign up to set email alerts
|

Contextual influences on employment of people with dual diagnosis: spinal cord injury and traumatic brain injury

Abstract: When considering the impact of contextual factors on paid employment for people with a dual diagnosis of spinal cord injury/traumatic brain injury, personal factors may be of greater influence than environmental factors. Study participants experienced few physical or attitudinal barriers and reported highly supportive interpersonal relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…( 2008 ) d Volker et al ( 2015 ) Wåhlin et al ( 2012 ) Waynor et al ( 2016 ) a Motivation Awang et al ( 2016 ) Boyle et al . ( 2014 ) d Braathen et al ( 2007 ) Lydell et al (2011) b, d Puolakka et al . ( 2008 ) f Saperstein et al ( 2011 ) Elfving et al .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…( 2008 ) d Volker et al ( 2015 ) Wåhlin et al ( 2012 ) Waynor et al ( 2016 ) a Motivation Awang et al ( 2016 ) Boyle et al . ( 2014 ) d Braathen et al ( 2007 ) Lydell et al (2011) b, d Puolakka et al . ( 2008 ) f Saperstein et al ( 2011 ) Elfving et al .…”
Section: Resultsunclassified
“…Of the eight quantitative studies which investigated the association between motivation and work participation (Table 1 : Awang et al 2016 ; Boyle et al 2014 ; Braathen et al 2007 ; Elving et al 2009; Lydell et al 2011 ; Puolakka et al 2008 ; Saperstein et al 2011 ; Wan Kasim et al 2014 ), five found a positive association (Awang et al 2016 ; Boyle et al 2014 ; Braathen et al 2007 ; Lydell et al 2011 ; Saperstein et al 2011 ). One additional quantitative study only found an influence of motivation for some forms of work participation (Puolakka et al 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, other factors than demographics and injury-related variables, such as differences in the environment or psychological resources that have not been accounted for in this study, may explain variation in LMP. In order to identify suitable intervention targets for an enhanced LMP of persons with SCI, future empirical and experimental research needs to address modifiable environmental and personal factors in relation to bodily capacity [15, 17, 4649]. In the comparison of the amount of work performed by employed people from the SCI and the general population, stratification by gender, age group and lesion level yielded small sample sizes in some cases precluding meaningful interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of function after cervical SCI is retarded by a moderate TBI in the contra lateral hemisphere (14). A high level of social support is vital to help these patients in their daily lives (19). In resource-limited settings, such as in Kenya, where support is inadequate, the risk is real in dual diagnoses patients of losing out on paid employment, concomitant emotional changes and increased dependence.…”
Section: Discussionmentioning
confidence: 99%